Macroeconomic and Technological Drivers of Banking Growth in Uzbekistan - Azizbek Tokhtabaev (Genius Journals, 2023)
This paper studies how economic growth and digital technology have influenced the development of the banking sector in Uzbekistan from 2019 to 2023. The analysis is based on data about GDP, household income, consumer loans, and digital payments. The results show that strong macroeconomic performance together with rapid digital transformation has expanded financial inclusion and strengthened the stability of the banking system. The findings suggest that sustainable banking growth in Uzbekistan depends on maintaining a balance between economic policy, technological innovation, and institutional development.
Keywords: banking growth; macroeconomic factors; digitalization